Childhood adverse life events, disordered eating, and body mass index in US Military service members. Issue 5 (2nd March 2018) - Bakalar, Jennifer L.; Barmine, Marissa; Druskin, Lindsay; Olsen, Cara H.; Quinlan, Jeffrey; Sbrocco, Tracy; Tanofsky‐Kraff, Marian
Abstract: Objective: US service members appear to be at high‐risk for disordered eating. Further, the military is experiencing unprecedented prevalence of overweight and obesity. US service members also report a high prevalence of childhood adverse life event (ALE) exposure. Despite consistent links between early adversity with eating disorders and obesity, there is a dearth of research examining the association between ALE exposure and disordered eating and weight in military personnel. Method: An online survey study was conducted in active duty personnel to examine childhood ALE history using the Life Stressor Checklist ‐ Revised, disordered eating using the Eating Disorder Examination ‐ Questionnaire total score, and self‐reported body mass index (BMI, kg/m 2 ). Results: Among 179 respondents, multiple indices of childhood ALE were positively associated with disordered eating. Traumatic childhood ALE and subjective impact of childhood ALE were associated with higher BMI and these associations were mediated by disordered eating. Discussion: Findings support evaluating childhood ALE exposure among service members with disordered eating and weight concerns. Moreover, findings support the need for prospective research to elucidate these relationships.